Computer vision for multimedia applications : methods and solutions - Cheng, Jian , 1977-; Jiang, Shuqiang , 1977-; Wang, Jinjun , 1977- (Information Science Reference, 2011)
"This book presents the latest developments in computer vision methods applicable to various problems in multimedia computing, including new ideas, as well as problems in computer vision and multimedia computing"--Provided by publisher